A Three-Dimensional Scale for the Qualitative and Quantitative Assessments of Secondary Alveolar Bone Grafting (SABG) in Unilateral Cleft Lip and Palate Patients Using Cone-Beam Computed Tomography (CBCT) - Kumar, Ashish; Batra, Puneet; Sharma, Karan; Raghavan, Sreevatsan; Talwar, Aditya; Srivastava, Amit; Sood, Sundereshwer Chander (Indian Journal of Plastic Surgery, 2022)
Background The objective of our study was to derive an objective assessment scale for three-dimensional (3D) qualitative and quantitative evaluation of secondary alveolar bone grafting (SABG) using cone-bone computed tomography (CBCT) in patients with unilateral cleft lip and palate (UCLP).Methods CBCT scans for pre- and 3-month post-SABG were reviewed for bone volume, height, width, and density of the bony bridge formed in the cleft defect in 20 patients with UCLP. Basic descriptive and principal component analysis was used to extract the various sub-components of the scale. Spearman's correlation was used to check the validity of the scale, and intra-class coefficient (ICC) and Cronbach's α were calculated to establish the reliability and retest applicability of the scale.Results Each CBCT scan was assessed in five areas: cementoenamel junction (CEJ), root apex, root midpoint, 3 and 6 mm below CEJ, and tabulated in percentiles of 20, 25, 40, 50, 60, and 75 for all the parameters (bone volume, density, and width). These scores were validated when correlated to the scale given by Kamperos et al. Cronbach's α for the domains demonstrated acceptable to excellent internal consistency. The ICC showed good test–retest reliability having a range of scores from 0.89 to 0.94.Conclusion The proposed scale for the 3D assessment of SABG in patients with UCLP provides gradation for the objective assessment of the bony bridge. This gradation enables the qualitative and quantitative assessments of the bony bridge, thus allowing each clinician to judge SABG more conclusively.
Keywords: Cone-beam CT; Three-dimensional scale; Cleft lip and palate; Bone grafting